Combined use of radiomics and artificial neural networks for the three‐dimensional automatic segmentation of glioblastoma multiforme - Mulet de Los Reyes, Alexander (2024)
Glioblastoma multiforme (GBM) is the most prevalent and aggressive primary brain tumor that has the worst prognosis in adults. Currently, the automatic segmentation of this kind of tumor is being intensively studied. Here, the automatic three-dimensional segmentation of the GBM is achieved with its related subzones (active tumor, inner necrosis, and peripheral edema). Preliminary segmentations were ﬁrst deﬁned based on the four basic magnetic resonance imaging modalities and classic image processing methods (multithreshold Otsu, Chan-Vese active contours, and morphological erosion). After an automatic gap-ﬁlling post processing step, these preliminary segmentations were combined and corrected by a supervised artiﬁcial neural network of multilayer perceptron type with a hidden layer of 80 neurons, fed by 30 selected radiomic features of gray intensity and texture. Network classiﬁcation has an overall accuracy of 83.9%, while the complete combined algorithm achieves average Dice similarity coeﬃcients of 89.3%, 80.7%, 79.7% and 66.4% for the entire region of interest, active tumor, edema, and necrosis segmentations, respectively. These values are in the range of the best reported in the present bibliography, but even with better Hausdorﬀ distances and lower computational costs. Results presented here evidence that it is possible to achieve the automatic segmentationof this kind of tumor by traditional radiomics. This has relevant clinical potential at the time of diagnosis, precision radiotherapy planning, or post-treatment response evaluation.